MODEL TPACK DAN VIDEO ANIMASI INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR AKHLAK PADA SISWA SEKOLAH DASAR - Kosesa, Mala Deni; Herianingtyas, Nur Luthfi Rizqa; Dewi, Rosbanon (Elementar : Jurnal Pendidikan Dasar, 2024)
This study aims to improve student learning achievement in Islamic Religious Education, specifically the moral lesson "Ayo Berperilaku Terpuji" (Let's Behave Nobly), through the implementation of the TPACK (Technological Pedagogical Content Knowledge) teaching model using interactive animated videos. The research was conducted with 2B grade students at SD Negeri 016 Tanjungpinang Timur during the first semester of the 2024/2025 academic year.The method used is Classroom Action Research (CAR), consisting of two cycles, each comprising four stages: planning, implementation, observation, and reflection. Data collection techniques were based on a quantitative approach, utilizing the results of summative tests administered after the lesson. The data analysis results show a significant improvement in student learning achievement. The percentage of students who reached the Minimum Completion Criteria (KKM) increased from 60% in the pre-cycle to 70% in cycle I, and reached 97% in cycle II Thus, the application of the TPACK teaching model with interactive animated videos was proven to be effective in improving student learning achievement, raising students' performance from  below average to good and very good.